Direct access to 2-amino-5-azidomethylfurans through palladium-catalyzed azidative cycloisomerization of homoallenyl amides. Issue 36 (22nd August 2016) - Huang, Qianwen; Zheng, Hanliang; Liu, Shuiyou; Kong, Lichun; Luo, Fang; Zhu, Gangguo
Abstract : A room temperature Pd-catalyzed azidative cycloisomerization of homoallenyl amides using TMSN3 as the azidation reagent and PhI(O2 CCF3 )2 as the oxidant is described, producing various 2-amino-5-azidomethylfurans in moderate to excellent yields. Abstract : A room temperature, efficient, and palladium-catalyzed azidative cycloisomerization of homoallenyl amides using TMSN3 as the azidation reagent and PhI(O2 CCF3 )2 as the oxidant is described, producing a variety of 2-amino-5-azidomethylfurans in moderate to excellent yields. The products can be applied to the concise synthesis of 1, 2, 3-triazoles via a Cu-catalyzed azide–alkyne cycloaddition.